Calitatea serviciilor în bibliotecile universitare: o sinteză pe baza publicațiilordin anii 2014-2020: Olesea Dobrea - admin, admin (BIBLIOPOLIS, 2022)
Nowadays, in order to be competitive and efficient in the information market, libraries need be user-centered, providing them quality products and services. University libraries have always strived to provide high quality services to its users. Quality management delivers tools as well as the direction of quality improvement. This paper aims to analyze and evaluate the Total Quality Management in university libraries with a view of examining the approaches in specialized publications. Thus, this article presents a synthesis of scientific publications about total quality management in libraries during 2014-2020 period. The paper examines the quality management implementation in library, as well as the use of various tools (LibQUAL+, SERVQUAL) that help librarians evaluate services, make decisions, and achieve better quality. This paper also provides information on total quality management and its benefits in providing services to library users.